Evidential analysis for computer generated animation (CGA) - Hussin, Norriza (2006)
The purpose of this thesis is to examine the items of legal evidence from cases, which have utilised Computer-Generated Animation (CGA) technology. In particular, it seeks to determine the degree of reliability and accuracy of CGA based on these items of legal evidence. The research design involved both quasi-experimental processes and pragmatic (sensitivity analyses). This design sought to examine the importance of evidence from a number of case studies and addresses the possible measures to be considered when generating such animations for litigation purposes.